Preparation, Characterization of (SBA-15)-TiO2 Nanocomposite Material and Its Application to Wiping Off Methylene Blue in Water Body - MA, YU-QIN; YU, HUI; MENG, RAO; JIN, XIN; ZHAI, QING-ZHOU; XU, JING-BO (Asian Journal of Chemistry, 2010)
Titania (TiO2) was incorporated into SBA-15 by solid phase thermal diffusion method and the prepared nanocomposite material was characterized by powder X-ray diffraction, Fourier transform infrared spectroscopy, nitrogen adsorption-desorption analysis, transmission electron microscopy and scanning electron microscopy. The results showed that for the (SBA-15)-TiO2 the frameworks and ordered mesoporous structures of the SBA-15 molecular sieve were kept well. When the (SBA-15)- TiO2 was used to remove the methylene blue in water body, the removal effect was good.